Respon Publik Terhadap Strategi Dakwah melalui Stand Up Comedy pada Platform YouTube - Risma Alviyanti; Nur Hidayat Muh Said (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Lifestyle trends across generations have an impact on da'wah strategies. The approach with the stand-up comedy method or humor on the YouTube platform is the most up to date alternative. This phenomenon is directly proportional to the high prevalence of YouTube users in Indonesia. So this descriptive research aims to analyze the sentiment of public response to religious content delivered through stand up comedy. The data source for this research is a YouTube video uploaded by Dzawin Nur with the topic “Kuliah Antum - Ustad Kembali #2.1”. Sentiment analysis uses web scraping techniques from YouTube Comment Extractor and PredictEsay based on Natural Language Processing (NPL). From the 1.006 randomly analyzed comments, 300 comments showed positive sentiment reaching 99.6%. Meanwhile, neutral and negative sentiments are only 0.2% each. Da'wah through stand up comedy is effective as a da'wah strategy in a form that is more relevant to the transformation of social dynamics.